Assessment of Tear Film Quality among Smokers Using Tear Ferning Patterns - Ali M. Masmali; Adil Al-Shehri; Saud A. Alanazi; Ali Abusharaha; Raied Fagehi; Gamal A. El-Hiti (Journal of Ophthalmology)
Purpose. To investigate the effect of cigarette smoking on the ocular tear film. Methods. Thirty healthy young male cigarette smokers (20–38 years old) and 30 healthy age matched nonsmokers were enrolled in the study. McMonnies questionnaire, slit lamp, and PRT test were used to screen the subjects. Tear samples were collected from the right eyes and tear ferning patterns were observed and graded. Results. The mean MacMonnies scores and TF grades were significantly higher in the smoker subjects (mean ± SD = 9.83±5.22 and 0.96±0.54, resp.) compared to nonsmokers (mean ± SD = 5.96±3.06 and 0.41±0.38, resp.). The mean values obtained from PRT and TBUT tests were 22.23±6.35 mm and 12.17±3.81 s for smokers and 22.16±5.63 mm and 14.13±2.62 s for nonsmokers, respectively. Strong correlations were found between MacMonnies scores and both PRT (r=0.596) and TF (r=0.516). There was statistically significant difference in TF grades (p=0.00), TBUT (p=0.036) and McMonnies (p=0.02) between smokers and nonsmokers. Conclusion. Cigarette smoking could have a significant effect on the tear film quality of the eye.